Isolating the impacts of anthropogenic water use within the hydrological regime of north India. Issue 5 (18th January 2020) - O'Keeffe, J.; Moulds, S.; Scheidegger, J.M.; Jackson, C.R.; Nair, T.; Mijic, A.
Abstract: The effects of anthropogenic water use play a significant role in determining the hydrological cycle of north India. This paper explores anthropogenic impacts within the region's hydrological regime by explicitly including observed human water use behaviour, irrigation infrastructure and the natural environment in the CHANSE (Coupled Human And Natural Systems Environment) socio‐hydrological modelling framework. The model is constrained by observed qualitative and quantitative information collected in the study area, along with climate and socio‐economic variables from additional sources. Four separate scenarios, including business as usual (BAU, representing observed irrigation practices), groundwater irrigation only (where the influence of the canal network is removed), canal irrigation only (where all irrigation water is supplied by diverted surface water) and rainfed only (where all human interventions are removed) are used. Under BAU conditions the modelling framework closely matched observed groundwater levels. Following the removal of the canal network, which forces farmers to rely completely on groundwater for irrigation, water levels decrease, while under a canal‐only scenario flooding occurs. Under the rainfed‐only scenario, groundwater levels similar to current business‐as‐usual conditions are observed, despite much larger volumes of recharge and discharge entering and leaving the system under BAU practices. While groundwater abstraction alone may lead to aquifer depletion, the conjunctive use of surface and groundwater resources, which includes unintended contributions of canal leakage, create conditions similar to those where no human interventions are present. Here, the importance of suitable water management practices, in maintaining sustainable water resources, is shown. This may include augmenting groundwater resources through managed aquifer recharge and reducing the impacts on aquifer resources through occasional canal water use where possible. The importance of optimal water management practices that highlight trade‐offs between environmental impact and human wellbeing are shown, providing useful information for policy makers, water managers and users. © 2019 John Wiley & Sons, Ltd. Abstract : Our understanding of the impacts of human water use on the hydrological cycle of north India are explored through field data collection and socio‐hydrological modelling.